"I Have a Wish": Anti-Asian Racism and Facing Challenges Amid the COVID-19 Pandemic Among Asian International Graduate Students. (March 2023) - Dong, Fanghong; Hwang, Yeji; Hodgson, Nancy A.
Introduction: Although Asian international graduate students (AIGS) were at risk for mental health problems during the pandemic, little is known about the experience of international students during COVID-19. This study aimed to examine the experiences of AIGS who lived in the United States during COVID-19. Method: This qualitative descriptive study included 22 participants from five large universities in Philadelphia. Semi-structured interviews were conducted during September and October 2020, and a thematic analysis was used for data analyses. Results: Three themes were found: (a) "We are left alone here": Being an international student; (b) "Stay busy" and "Do something": Being a graduate student; and (c) "I have a wish": Seeking for support, perceived support, and preferred counseling services as a self-advocator. Discussion: Help is needed for AIGS to navigate uncertainties, provide proper coping skills, make efforts against anti-Asian racism, and provide culturally based mental health resources.